Skjellressurser i Sydishavet: litteraturstudie - Jakobsen, Øystein; Fiskeridirektoratet (Norges fiskerihøyskole, 1988)
Keywords: Sørishavet; marinbiologi; skjell

Resting spore formation in the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo - Syvertsen, Erik E. (Polar Biology, 1985)
The resting spore morphology of the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo are described. Both species form endogenous resting spores. The spore valve of C. furcatus differ from those of the vegetative cells primarily by (i) a greater convexity and (ii) a coarser and more distinctly fasciculated areolation. This resting spore is identical to the diatom traditionally identified as C. stellaris var. symbolophorus (Grunow) Jørgensen in the Antarctic. The resting spore of T. australis differs from the vegetative cells by (i) a lack of clusters of strutted processes in a modified ring on valve face, (ii) a coarser areolation and tangential rows of areolae and (iii) a narrower and more simply structured girdle. The resting spore valve of T. australis has been described as belonging to a separate species, Actinocyclus excentricus Peragallo.
Keywords: Sørishavet; diatomeer; marinbiologi

Biokjemiske studier over antarktisk krill - Ellingsen, Trond E; Norges tekniske høgskole Institutt for teknisk, biokjemi (Institutt for teknisk biokjemi, 1982)
Keywords: Bouvetøya; Sørishavet; Weddellhavet; biokjemi; krill; lipider; lyskreps; marinbiologi

Krill: mat i mengder i Sørishavet - Sakshaug, Egil (Syn og segn, 1982)
Keywords: Sørishavet; krill; marinbiologi

Konvensjon om bevaring av marine levende ressurser i Antarktis = Convention on the Conservation of Antarctic Marine Living Resources (Lovdata, 1980)
Keywords: Sørishavet; forvaltning; jus; marinbiologi; miljøvern; naturvern